(untitled) (Global Journal of Science Frontier Research, 2018)
According to the current ’Material-Causal’ Paradigm underlying both Relativity Theory and Quantum Mechanics, "time" is an "observerdependent", "uni-directional", "material-causal" entity: Its "flow" is "unidirectional", i.e., it can only move from the "present" to the "past" but not from the "future" to the "past"… This is because, according to Relativity Theory, nothing can travel faster than the speed of light so no observer can "catch" any light signal emanating from any "past" even". According to Quantum Mechanics, following the "collapse" of the subatomic target’s "probability wavefunction" as "caused" by its direct physical interaction with a corresponding subatomic "probe" element – e.g., into a single (space-energy, temporal-mass) value, it is not possible to "un-collapse" this singular ("collapsed") target value back into the (preceding) multifarious "probability wave function" state… Hence, "time-reversal" is not possible according to both Relativity Theory and Quantum Mechanics, which are underlie by the Old "Material-Causal" Paradigm of 20th century Theoretical Physics;